(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Gestational diabetes mellitus (GDM) is one of the most common endocrine disorders during pregnancy, significantly affecting maternal and fetal health. The pathogenesis of GDM involves a combination of maternal insulin resistance and inadequate β-cell compensation, disturbances in lipid metabolism, and increased oxidative stress. These processes lead to morphological and functional changes in the placenta, including villous thickening, fibrosis, microcirculation impairment, and increased placental mass. Placental alterations in GDM are directly associated with a higher risk of fetal macrosomia, preeclampsia, and preterm delivery, and may contribute to long-term metabolic risk in offspring. This review systematizes current data on the pathophysiology of GDM, mechanisms of maternal hyperglycemia–placenta interaction, placental morphofunctional changes, and contemporary methods of assessment, highlighting the importance of early detection and monitoring to reduce perinatal complications.